2022
DOI: 10.1111/jfpe.14254
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of continuous flow pulsed light system process parameters for microbial inactivation in tender coconut water, pineapple and orange juice

Abstract: Continuous flow pulsed light (PL) system was designed and fabricated with a residence time of 3.5 s at a flow rate of 100 ml/min to study the effect on microbial quality of the fruit juice. The circuit was designed to deliver pulse energy between 12.6 and 756 J/cm 2 with a flash lasted 360 μs at a frequency of three pulses per second. Tender coconut water, pineapple and orange juice was treated with different input voltage (500-1000 V) to the lamp, distance of the lamp exposed to the sample (5-15 cm) and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Further, Kaya et al 25 reported that in verjuice beverage PL could inactivate 0.96 ± 0.27 log cfu mL −1 in S. cerevisiae even after delivering a dose of 34 J cm −2 and being placed 5 mm away from the lamp. Preetha et al 26 reported a maximum log reduction of 5.54 cfu mL −1 of APC populations observed in tender coconut water followed by pineapple and orange juice with 5.38 and 5.24 log reductions by treating them with higher energy of 729 J cm −2 . The inactivation of microbes depended on the properties of light absorption by the fruit juices.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Kaya et al 25 reported that in verjuice beverage PL could inactivate 0.96 ± 0.27 log cfu mL −1 in S. cerevisiae even after delivering a dose of 34 J cm −2 and being placed 5 mm away from the lamp. Preetha et al 26 reported a maximum log reduction of 5.54 cfu mL −1 of APC populations observed in tender coconut water followed by pineapple and orange juice with 5.38 and 5.24 log reductions by treating them with higher energy of 729 J cm −2 . The inactivation of microbes depended on the properties of light absorption by the fruit juices.…”
Section: Resultsmentioning
confidence: 99%
“…With advantages such as requiring low temperatures, rapid processing time, and being environmentally friendly, PEF is rapidly gaining attention as a promising food processing technology (Manzoor et al, 2019a,b;Rahaman et al, 2020;Lal et al, 2021). PEF causes negligible damage to food nutrients compared to traditional food processing techniques and can eliminate some hazardous microorganisms to extend the preservation time of food (Soliva-Fortuny et al, 2009;Napotnik et al, 2016;Peng et al, 2016;Liu C. Y. et al, 2021;Nabilah et al, 2022;Preetha et al, 2023). Most research in PEF has focused on active substance extraction, pasteurization, and the drying and thawing of food products, and there is relatively little research on the influence of PEF on biometabolic pathways that induce the synthesis of nutrients in food products (Boussetta et al, 2011(Boussetta et al, , 2012Rahaman et al, 2019;Ahmed et al, 2020;Preetha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%